Calling Higher Education Leaders: Which Departments on Your Campus Serve Displaced Learners? - Unangst, Lisa (Journal of International Students, 2022)
Particularly in the last eight years, many calls have been issued for postsecondary education stakeholders to imagine new pathways for displaced learners seeking access to degree programs. Here, “displaced learners” encompasses refugees, asylees, and individuals holding other legal statuses indicating temporary protection; these nationally-specific categories are constructs that may overlap with international student status (Oliveira & Kentor, 2020; Vigil & Abidi, 2019). While progress has been made – according to UNHCR (2022), only 5% of refugees access higher education worldwide at present, up from 3% in 2020 – it is clear that much more focused attention is required. In this piece, I am speaking specifically to college and university presidents as I ask: how is your campus serving displaced learners? Which departments are engaged, and what resources would you need to expand your offerings? What follows below is a list of questions posed to senior leaders in the United States and internationally, where diverse public and private institutions host initiatives that could be tailored to serve lifelong learners with histories of displacement, and with many campuses making significant investments in relevant areas including support for marginalized students and global engagement. This checklist is intended to underscore good practices and the role of institutional silos.